2013
DOI: 10.1148/radiol.13121990
|View full text |Cite
|
Sign up to set email alerts
|

Knee Derangements: Comparison of Isotropic 3D Fast Spin-Echo, Isotropic 3D Balanced Fast Field-Echo, and Conventional 2D Fast Spin-Echo MR Imaging

Abstract: The performance of IW fast SE is superior to that of balanced FFE in evaluation of cartilaginous defects, with no significant difference in performance between 2D fast SE, 3D IW fast SE, and 3D balanced FFE in evaluation of meniscal and ligament tears. Subchondral bone marrow signal abnormality is more easily seen on 3D IW fast SE images, with better subjective image quality and fewer artifacts, than on images obtained with other techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 31 publications
6
35
0
Order By: Relevance
“…Similar to previous studies of 3D MRI, there was a very good interreader agreement in our study . The overall image quality was high, and the degree of motion artifacts was low, which was similar to the quality of 3D MRI in adults …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to previous studies of 3D MRI, there was a very good interreader agreement in our study . The overall image quality was high, and the degree of motion artifacts was low, which was similar to the quality of 3D MRI in adults …”
Section: Discussionsupporting
confidence: 89%
“…Although comparison with the performance of 3D MRI for the diagnosis of internal derangement in adults is limited due to differences between immature and mature knees, the diagnostic performance of our 10‐min 3D MRI protocol compares favorably as well. Prior studies in adults found sensitivities, specificities, and accuracies of 85–100%, 68–95%, and 79–97% for diagnosing medial meniscal tears, 58–95%, 82–96%, and 74–94% for lateral meniscal tears, 90–100%, 80–98%, and 89–99% for anterior cruciate ligament tears, and 100%, 97–100%, and 97–100% for posterior cruciate ligament tears . Similar to previous studies of 3D MRI, there was a very good interreader agreement in our study .…”
Section: Discussionsupporting
confidence: 79%
“…[2][3][4] However, other 3-T studies have shown promising results for the evaluation of menisci by a 3D sequence with no statistical difference in the evaluation of surgically confirmed meniscal tears. 5,6 A larger study by Kijowski and associates demonstrated that a 3D SPACE sequence had a similar sensitivity and specificity for evaluating medial meniscal tears compared with a routine MRI protocol and a similar specificity in evaluating the lateral meniscus but a significantly reduced sensitivity. 7 Studies at 3 T have shown that optimized 3D SPACE provides significantly higher signal and contrast than conventional 2D FSE, particularly for fluid and cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Up until now, the majority of studies assessing 3D SE sequences in the knee have been undertaken on 3-T MRI systems. [2][3][4][5][6][7][8][9][10][11] However, in common with many centres, our institution employs a 1.5-T system for the majority of its routine knee MRI studies. With acquisition time being a key factor in knee imaging protocols, our aim was to assess whether reconstructions obtained from a single isotropic 3D FSE PD (FS) sequence could replace the 3 PD (FS) sequences in our standard protocol on a 1.5-T system (Siemens Avanto, Erlangen, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…3D sequences, such as SPACE on Siemens scanners and CUBE on GE scanners, may have a longer acquisition time than conventional sequences, but the ability to reconstruct images in any plane allows one to potentially replace multiple 2D images. Recent research has suggested that the use of limited 3D sequences with subsequent reconstruction in different planes can perform similarly to traditional 2D imaging in evaluation of the meniscus, ligaments, cartilage, and bone marrow . 3D images may be particularly beneficial for visualizing areas that have traditionally been difficult to assess on 2D images, particularly the meniscal roots and trochlear cartilage .…”
Section: D Sequencesmentioning
confidence: 99%